A descriptive analysis of anglicisms used in Ecuadorian Magazines - Gonzalez Rodriguez, Rina Esperanza (2010)
The theme for our research project is ―A DESCRIPTIVE ANALYSIS OF ANGLICISMS IN ECUADORIAN MAGAZINES‖. Since this is a current phenomenon in our society, which has shown up within the last few years, its focus of attention is over their linguistic role in Ecuadorian magazines. The ―Universidad Técnica Particular de Loja‖ has launched a project that has to be carried out by the pre-graduate students of English all over Ecuador, and this particular investigation has been done in the city of Azogues where all kinds of magazines were found, from cultural ones to scholarly and those of general interest.